HUBUNGAN STRES KERJA DENGAN ADAPTASI PADA PERAWAT DI INSTALASI GAWAT DARURAT RSUD PANDAN ARANG BOYOLALI - Danang Prasetyo Utomo; Sulastri Sulastri (Universitas Muhammadiyah Surakarta, 2009)
The nurse in Emergency room faces various aspect in their working environment. Work in emergency instalation of RSUD Pandan Arang is categorized as a hard work, because the high quantity of the patien who on their is 85% BOR, the nurses are only 16 people, then the standard is 38 people. This condition makes the nurse stress. If the nurse can face the stressor well, it can result adaptive adaption, and if the nurse cannot find a good solution it can make a maladaptive adaptation. This research is to know the characteristics of the nurse, the description of stress and the nurse adaptation, the relationship between work stress and nurse adaptation in emergency instalation of RSUD Pandan Arang Boyolali. Metode Research is the type of this research is non-experimental research with Descriptive Corelation method and using Cross Sectional approach. The technique of sampling is Total Sampling with the sample is 16 respondents. The validity test using product moment test and the reability test using Alpha Cronbach test. Then, to anayze the data is using Kendal tau-b test. The result of this research indicate that the result of Kendal tau-b analysis show the calculating value -0,597 with the probability 0,002 (p